Rapamycin attenuates Th2-driven experimental allergic conjunctivitis - Shin, Soojung; Lee, Ji Hyun; Lee, Hyun Jung; Chang, Sun Young; Chung, So Hyang (Clinical Immunology, 2018)
Allergic conjunctivitis is mediated by eosinophilic infiltration and Th2 type immune responses. This study aims to elucidate the role of rapamycin, mTOR inhibitor, on OVA-induced experimental allergic conjunctivitis (EAC). Rapamycin administration intraperitoneally markedly reduced clinical signs, total and OVA-specific IgE and IgG1/G2a ratio in serum, and conjunctival eosinophilic infiltration. Infiltrations of CD11c+ dendritic cells and CD4+ T cells, and the expressions of chemokines and adhesion molecules in the conjunctiva were attenuated in rapamycin-treated mice, as well as decreased Th1 and Th2 cytokines in the cervical lymph nodes compared to non-treated mice. The expression of mTOR signaling proteins was increased in EAC and reduced by rapamycin treatment. Topical application of rapamycin was also proved to show reduced clinical signs, eosinophil infiltration, and Th2 type immune responses comparable to those from intraperitoneal injection of rapamycin. These findings suggest the therapeutic implications of rapamycin in the attenuation of allergic conjunctivitis.
Keywords: Animals; Conjunctiva; Conjunctivitis, Allergic; Female; Gene Expression; Immunoglobulin E; Immunoglobulin G; Immunosuppressive Agents; Mice, Inbred BALB C; Ovalbumin; Sirolimus; Th2 Cells; Allergic conjunctivitis; Dendritic cells; Eosinophil; Rapamycin; Th2 type immune response